Implementation of the Mayor of Bontang’s Circular Letter on the Statement of Physical Land Possession: A Case Study of Bontang Barat District - Ramly Ramly; Kus Indarto; Hariati Hariati (Universitas Pancasakti, 2026)
This study aims to analyze the implementation of the Bontang Mayor's Circular Letter concerning the Statement of Physical Land Control in West Bontang District as an administrative policy instrument in local land governance, which emerged in response to the gap between de facto land control practices in the community and the formal land system that requires proof of de jure ownership. This study uses a qualitative approach with a descriptive analytical method, where data is obtained through in-depth interviews with village and sub-district officials, community leaders, and residents directly involved in the process of processing the statement of physical land control, supplemented by limited observation and policy documentation studies. Data analysis is carried out through the stages of reduction, presentation, and drawing conclusions by maintaining data validity through triangulation of sources and methods. The results of the study indicate that the implementation of the Bontang Mayor's Circular Letter takes place contextually and is greatly influenced by the capacity of implementing officials, bureaucratic discretion, as well as the social context and local power relations that develop in the community. This policy was relatively effective in providing temporary administrative recognition and building social legitimacy for land ownership, but on the other hand, it also gave rise to procedural variations, inconsistent service delivery, and differences in public understanding regarding the legal status of the declaration. This finding confirms that the effectiveness of local land policies is determined not only by the smoothness of the administrative process, but also by the clarity of policy communication, the management of apparatus discretion, and the ability of local governments to integrate local administrative policies with the national land reform system and agenda to realize fair, accountable, and inclusive land governance.